High-speed extrusion of heat-treatable Mg–Al–Ca–Mn dilute alloy. (May 2015) - Nakata, T.; Mezaki, T.; Ajima, R.; Xu, C.; Oh-ishi, K.; Shimizu, K.; Hanaki, S.; Sasaki, T.T.; Hono, K.; Kamado, S.
Abstract: A newly developed dilute magnesium alloy, Mg–0.27Al–0.13Ca–0.21Mn (at.%), shows extraordinary high-speed extrudability of a die-exit speed of 60 m/min. Subsequent artificial aging at 200 °C (T5) enhanced the proof stress from 170 MPa to 207 MPa due to the precipitation of Guinier Preston (G.P.) zones and weakened basal texture while keeping good ductility of 12.5%. High-speed extrusion reduces the processing cost, so the dilute Mg–Al–Ca–Mn alloy could be an industrially viable low-cost medium strength structural material.